Acute and Chronic Responses of Aerobic Exercise With Blood Flow Restriction: A Systematic Review - Silva, Júlio Cesar Gomes; Pereira Neto, Elísio Alves; Pfeiffer, Patrick Alan Souza; Neto, Gabriel Rodrigues; Rodrigues, Amanda Santos; Bemben, Michael G.; Patterson, Stephen D.; Batista, Gilmário Ricarte; Cirilo-Sousa, Maria S. (Frontiers in Physiology, 2019)
This study systematically reviewed the available scientific evidence pertaining to the acute and chronic changes promoted by aerobic exercise (AE) combined with blood flow restriction (BFR) on neuromuscular, metabolic and hemodynamic variables. PubMed, Web of ScienceTM, Scopus and Google Scholar databases were searched for the period from January 2000 to November 2017 and the analysis involved a critical review of the contents. A total of 226 articles were identified, of which 199 articles were excluded and 27 articles satisfied the selection criteria. Six studies evaluated the acute effects and seven studies evaluated the chronic metabolic effects of AE + BFR. For the neuromuscular variables, two studies analysed the acute effects of AE + BFR and eleven studies analysed the chronic effects. Only nine studies were identified that evaluated the hemodynamic acute effects of AE + BFR. The analysis provided evidence that AE combined with BFR promotes positive acute and chronic changes in neuromuscular and metabolic variables, a greater elevation in hemodynamic variables than exercise alone, and a higher energy demand during and after exercise. Since these alterations were all well tolerated, this method can be considered to be safe and feasible for populations of athletes, healthy young, obese and elderly individuals.